The Impact of Self-Care Counseling on Quality of Life in Pregnant Women with Gestational Hypertension - Golnaz sadat Ahmadinejad; Talat Khadivzadeh; Mitra Eftekharyazdi; Habibollah Esmaeili (Mashhad University of Medical Sciences, 2022)
Background & aim: Pregnancy with high blood pressure is one of the high-risk pregnancies and requires more healthcare to prevent maternal and fetal complications. Therefore, this study was designed to investigate the effect of self-care counseling on quality of life in pregnant women with hypertension.Methods: This clinical trial was performed on 90 pregnant women with gestational hypertension referred to Sabzevar health centers between 2021 and 2022. Sample were selected by convenience sampling and divided into intervention and control groups by random assignment. In addition to receiving routine care sessions, the intervention group received four 45- to 60-minute sessions of self-care counseling according to the GATHER model each week. The control group received routine care. Data were collected using a quality of life questionnaire (sf-36) and analyzed by SPSS software version 25 using independent and paired t-test, Mann-Whitney and analysis of covariance.Results: There was no significant difference in the mean quality of life score in the intervention and control group (47/33 ± 5/65 vs 49/77 ± 5/55) before intervention. However, after the intervention, there was a significant difference between the two groups (p <0/001). The mean score of quality of life in the intervention group was 76/07 ± 5/01 and in the control group was 48/73 ± 6/75.Conclusion: Considering the effect of self-care counseling on quality of life improvement in pregnant women with hypertensive disorders, it is recommended to tailor and implement such counseling interventions to increase quality of life in these vulnerable population during pregnancy.